Os desafios para a salvaguarda do patrimônio cultural em territórios minerários no Quadrilátero Ferrífero de Minas Gerais - Juliana Gomes Parreiras (2023)
This research seeks to investigate, according to the analysis categories and interpretation paradigms of Cultural Geography and Political Ecology, the situation in which Cultural Heritage finds itself in territories of the Iron Quadrangle of Minas Gerais - QF due to the activities of mineral exploration in the region, having as its thematic focus the Built Cultural Heritage protected by the State agency (IEPHA – State Institute of Historical and Artistic Heritage of Minas Gerais) and by the National agency (IPHAN – National Historical and Artistic Heritage Institute). The research seeks to verify the possible impacts caused to cultural assets within the context of the QF in a mineral-dependence framework and the consequences for the enjoyment and autonomy to maintain these assets. Given the panorama of rigid locational minerals and the concentration of significant cultural heritage - which are historically related -, the QF region has gained international recognition and visibility, however, there is a significant challenge in maintaining this heritage to the detriment of the implementation and expansion of mineral exploration. Understanding Cultural Heritage as a supranational fundamental right of a collective and diffuse nature of the human person, the current contradictory debate between sustainable development and the neoliberal context, highlights the urgency in analyzing the instruments and strategies used by capital – benefactor or threat? – and by the State to guarantee the safeguarding of essential characteristics of this cultural heritage, always understanding its material and immaterial aspects as integral and inseparable. This research is methodologically constructed from exploratory research, supported by a qualitative approach of an applied nature, with Territory as the central analytical category and including environmental, social, cultural and political dynamics as a product of these territorial relations.